Stage Distribution of Breast Cancer Diagnosed Before and After Implementation of Population-Based Mammographic Screening - Hofvind, S.; Skaane, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: The German mammographic screening program is very similar to the Norwegian Breast Cancer Screening Program (NBCSP), which started about 10 years earlier. This study analyzes the stage distribution of invasive breast cancers diagnosed in the pre-screening and screening period, and evaluates the overall mortality in women aged 55 – 74 in the pilot and non-pilot counties of the NBCSP. Materials and Methods: The NBCSP invites women aged 50 – 69 to participate in two-view mammography biennially. Chi-square statistics were used to compare percentages of the stage and treatment of invasive breast cancers diagnosed in women residing in the four pilot counties in the pre-screening (1984 – 1995) and screening (1996 – 2007) period. An ecological approach was used to analyze the age-specific mortality in the pilot and non-pilot counties for the period 1970 – 2007. Results: 50 % of the breast cancers diagnosed in the pre-screening period, 70 % of the cases detected with screening, 43 % of the interval cancers, and 52 % of the cancers diagnosed outside the NBCSP were stage I. Stage III + was present in 11 % of the cancers in the pre-screening period, and in 1 % of the cancers detected with screening. In the screening period, the breast cancer mortality rate decreased substantially more in the pilot counties than in the non-pilot counties. Conclusion: The stage distribution of breast cancer diagnosed in the NBCSP is prognostically favorable compared to cancers diagnosed outside the screening program. The reduction in the breast cancer mortality rate was more pronounced in the four pilot counties compared to the non-pilot counties. It is necessary to evaluate the program based on individual data.
Keywords: breast; mammography; screening